NUEVOS HORIZONTES DEL PERIODISMO DEPORTIVO ESPAÑOL: PRIMERAS REVISTAS PARA MÓVILES Y TABLETAS EN LOS DIARIOS MARCA Y SPORT - José Luis ROJAS TORRIJOS (Fonseca, Journal of Communication, 2023)
Sports daily newspapers, like Marca and Sport, started publishing new tablet and mobile magazines in order to provide a response to the growing number of users who access to news of their favourite teams at anytime and from anywhere. These products complement newspapers content on their printed media and digital editions, by expanding coverage to less popular sports,exploring the innovation and giving sports information a closer approach, behaving as a more entertainment-oriented platform.